Evaluating Factors Related to the Abuse of Oral Corticosteroids among Community Pharmacy Customers: Using Theory of Reasoned Action - Ali Azeez Al-Jumaili; Bashar G Alfetlawi; Munaf H Zalzala (University of Minnesota Libraries Publishing, 2020)
Introduction: Although it is discouraged, community pharmacy customers can obtain oral corticosteroids (OCSs) without prescriptions from some community pharmacies in Iraq. Medication abuse is defined as the use of medication for non-medical reasons. Objectives: The study aimed to determine demographics, beliefs, and perceptions associated with the abuse of oral corticosteroids for non-illness reasons among community pharmacy customers. Methods: This cross-sectional study was conducted in fall 2018 in four provinces in Iraq. Customers of 19 community pharmacies asking for OCSs for themselves without a prescription were administered a paper survey. This study used the Theory of Reasoned Action (TRA) to measure the relationship between the motivational factors and the abuse of OCSs. Logistic regression analysis was conducted to evaluate the relationships between the use of OCSs for non-illness and six TRA factors: Normative belief, behavioral belief, evaluation of the behavior, motivation to comply, subjective norms and attitude toward behavior. Results: The study enrolled 141 participants (98 women and 43 men) taking asking for OCSs without prescription. Dexamethasone was the most commonly used OCSs (59.6%). Friends were the primary recommenders for corticosteroids abuse (28.4%). The main reasons for using OCSs were to increase appetite and gain weight (53.9 %). Approximately one-third (36.2 %) of the participants gained weight after using OCSs.  The regression analysis of the TRA variables showed two factors were significantly related to the abuse of OCSs. Age had a significant inverse relationship with the abuse of OCSs and the "good appearance" belief had a significant positive association with OCS abuse. Conclusion: Some Iraqi community pharmacy customers use non-prescribed oral corticosteroids to increase appetite and gain weight. Improve body appearance represents the dominant incentive that urges people to use OCSs without prescription. Health officials and healthcare practitioners need to promote people's awareness about the risks of misusing OCSs through education programs and advertisements in public health settings, media, and social media.   Article Type: Original Research